"Chop and change": Examining the occurrence of squad rotation and its effect on team performance in top European football leagues - Mehta, S.; Bassek, M.; Garnica-Caparros, M.; Memmert, D. (International Journal of Sports Science & Coaching, 2024)
The occurrence of squad rotation in football and its effect on team performance in terms of points have not been comprehensively studied in football performance analysis literature. This study deploys a data-driven approach to examine the occurrence of squad rotation across English, French, Italian and Spanish leagues over multiple seasons. It aims to establish the relationship observed between average squad rotations in starting lineups and end-of-season points. A total of 16,720 matches dating from the 2010/11 to 2021/22 seasons were analysed for average rotations in each team involved and the respective team's end of season points, alongside contextual information such as injury and logarithmic market value. A linear mixed-effects model was used to study this relationship, with each variable as well as interaction of variables being analysed for fixed effects. The results show that a significant relationship exists between team success, average rotation of the team per match and market value of the team, while no significant effects are found for injuries. The results describe how universally deploying squad rotation may not yield higher points over a season, but also shows how the effect of rotations on team success keep increasing as the market value of teams increases.